2006
DOI: 10.1117/12.695743
|View full text |Cite
|
Sign up to set email alerts
|

A radio frequency controlled microvalve for biomedical applications

Abstract: In this paper we propose the use of a RF controlled microvalve for implementation on a PZT substrate for biomedical applications. Such device has a huge range of applications such as parallel mixing of photo-lithographically defined nanolitre volumes, flow control in pneumatically driven microfluidic systems and lab-on-chip applications. The microvalve makes use of direct actuation mechanisms at the microscale level to allow its use in vivo applications. A number of acoustic propagation modes are investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Hence, the flow becomes directional. Cantilever structures (similar to those in Figure 2) are also commonly used as valve structures and have been shown to be amenable to active control using piezoelectric and RF modulation (Dissanayake et al 2007). …”
Section: Dynamic Geometrymentioning
confidence: 99%
“…Hence, the flow becomes directional. Cantilever structures (similar to those in Figure 2) are also commonly used as valve structures and have been shown to be amenable to active control using piezoelectric and RF modulation (Dissanayake et al 2007). …”
Section: Dynamic Geometrymentioning
confidence: 99%
“…The main PSicmapurap Displacement AmSlySie actuation mechanisms are piezoelectric actuation, electrostatic actuation, electromagnetic actuation, pneumatic actuation, Shape Memory Alloy (SMA) actuation, thermo-pneumatic actuation and bimetallic actuation. 13 Of these mechanisms, piezoelectric actuators are known for low power consumption and high force generation, 14 though the actuation displacement is comparatively lesser and fabrication requirements are fairly complex. Whereas electrostatic actuators generate a comparatively faster response time and shows a good reliability, even though the small force generated and comparatively smaller stroke are not attractive.…”
Section: Different Microactuation Mechanismsmentioning
confidence: 99%
“…1 Based on the previous work carried out by the authors 1,3,4 it is been demonstrated that the required wireless and batteryless actuation for a microfluidic device is achievable using a fully passive system. Initially, the micropump structure is designed by integrating a SAW device and a micropump chamber, which causes the microfluidic modulation.…”
Section: Microfluidic Devices For Drug Deliverymentioning
confidence: 99%